Mechanistic Characteristics of Surface Modified Organic Semiconductor g-C3N4 Nanotubes Alloyed with Titania - Sim, L.C.; Tan, W.H.; Leong, K.H.; Bashir, M.J.K.; Saravanan, P.; Surib, N.A. (MDPI, 2017)
The visible-light-driven photocatalytic degradation of Bisphenol A (BPA) was investigated using the binary composite of alkaline treated g-C3N4 (HT-g-C3N4) deposited over commercial TiO2 (Evonik Degussa GmbH, Essen, Germany). The existence and contribution of both TiO2 and g-C3N4/HT-g-C3N4 in the composite was confirmed through various analytical techniques including powder X-ray diffraction (XRD), high-resolution transmission electron microscopy (HRTEM), field emission scanning electron microscopy (FESEM), Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), ultraviolet-visible diffuse reflectance spectra (UV-vis-DRS), and photoluminescence (PL) analysis. The results showed that the titania in the binary composite exhibited both pure rutile and anatase phases. The morphological analysis indicated that the spongy "morel-like" structure of g-C3N4 turned to nanotube form after alkaline hydrothermal treatment and thereby decreased the specific surface area of HT-g-C3N4. The low surface area of HT-g-C3N4 dominates its promising optical property and effective charge transfer, resulting in a deprived degradation efficiency of BPA two times lower than pure g-C3N4 The binary composite of HT-g-C3N4/TiO2 exhibited excellent degradation efficiency of BPA with 2.16 times higher than the pure HT-g-C3N4. The enhanced photocatalytic activity was mainly due to the promising optical band gap structure with heterojunction interface, favorable specific surface area, and good charge separation.